Tratamiento contable de los arrendamientos y la razonabilidad de los estados financieros en las empresas del sector bananero - Espinel Muñoz, Samuel Alejandro (2023)
The main objective of this research is to analyze the influence of financial leasing on the ROA, ROE and AP profitability indicators of companies in the Ecuadorian banana sector in the period 2019 and 2020. The research carried out was of a descriptive and correlational nature, and of a nonexperimental design, the methodology used is According to the analysis of the research carried out by Pinto (2015); Obiero (2014); Muhammad, J.K., Naveed, K., Hammad H.M. (2012) and Wanjiru (2011), who in their research determine the effect of leasing financing that companies have on the economic and financial situation. For this, a sample of companies in the Ecuadorian banana sector was prepared, in the years 2019 and 2020, after which an analysis of the financial statements was carried out, calculate ratios to determine the impact of leases on profitability.......